2019
DOI: 10.1111/jgs.15956
|View full text |Cite|
|
Sign up to set email alerts
|

Comparisons between Oral Anticoagulants among Older Nonvalvular Atrial Fibrillation Patients

Abstract: OBJECTIVES Older adult patients are underrepresented in clinical trials comparing non–vitamin K antagonist oral anticoagulants (NOACs) and warfarin. This subgroup analysis of the ARISTOPHANES study used multiple data sources to compare the risk of stroke/systemic embolism (SE) and major bleeding (MB) among very old patients with nonvalvular atrial fibrillation (NVAF) prescribed NOACs or warfarin. DESIGN Retrospective observational study. SETTING The Centers for Medicare & Medicaid Services and three US commerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 35 publications
4
42
0
1
Order By: Relevance
“…Our results show that the annual rates of major bleeding in patients with NVAF aged ≥ 85 years were 3.1 and 4.2/100 PY with DOACs and warfarin, respectively. These incidences were comparable to those associated with OAC therapy in previous studies (ARISTOPHANES 4.9–8.5/100 PY; PREFER in AF 4.0–4.2/100 PY; START2-REGISTER 2.2–2.5/100 PY; Shinohara et al 1.5/100 PY; Yamaji et al 2.5–5.0%/year) [ 13 , 17 , 32 – 34 ]. Interestingly, gastrointestinal bleeding was the most common cause of major bleeding, followed by subdural hemorrhage and traumatic hemorrhage in our very elderly patients.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Our results show that the annual rates of major bleeding in patients with NVAF aged ≥ 85 years were 3.1 and 4.2/100 PY with DOACs and warfarin, respectively. These incidences were comparable to those associated with OAC therapy in previous studies (ARISTOPHANES 4.9–8.5/100 PY; PREFER in AF 4.0–4.2/100 PY; START2-REGISTER 2.2–2.5/100 PY; Shinohara et al 1.5/100 PY; Yamaji et al 2.5–5.0%/year) [ 13 , 17 , 32 – 34 ]. Interestingly, gastrointestinal bleeding was the most common cause of major bleeding, followed by subdural hemorrhage and traumatic hemorrhage in our very elderly patients.…”
Section: Discussionsupporting
confidence: 85%
“…Our results showed that the annual rates of ischemic stroke or systemic embolism in patients with NVAF aged ≥ 85 years were 1.8 and 2.2/100 PY with DOACs and warfarin, respectively. A retrospective analysis from a US database study (ARISTOPHANES) showed that the annual rates of ischemic stroke or systemic embolism in patients with NVAF aged ≥ 80 years (mean CHA 2 DS 2 -VASc score 4.7–4.8) were 1.4–1.6 and 2.0–2.1/100 PY with DOACs and warfarin, respectively [ 17 ]. A subanalysis of a European registry study (PREFER in AF) showed an annual rate of thromboembolic events of 4.3/100 PY in patients with NVAF aged ≥ 85 years (mostly taking vitamin K antagonists; mean CHA 2 DS 2 -VASc score 4.7) [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, in line with randomized studies, differences in safety outcomes between NOACs were seen. Apixaban was associated with a significantly lower major bleeding and intracranial bleeding risk as compared to VKAs in ≥75 and ≥80 year old AF patients (Deitelzweig et al, 2019;Hohmann et al, 2019;Alcusky et al, 2020;Wong et al, 2020). Importantly, as the ARISTOTLE trial did not provide data on the gastrointestinal bleeding risk of apixaban in older AF patients, observational studies were reassuring, illustrating a similar (Wong et al, 2020).…”
Section: Observational Studiesmentioning
confidence: 99%